Comparison of European system for cardiac operative risk evaluation (EuroSCORE) II with the postoperative outcomes in patients undergoing cardiac surgery (Journal of Fatima Jinnah Medical University, 2019)
Background: Models have been developed to predict a variety of outcomes, for all cardiac surgery and also for specific cardiac surgery procedures. The most broadly utilized model for anticipating mortality in cardiovascular surgery was EuroSCORE I which has been upgraded in recent times to EuroSCORE II. The objective of the present study was to evaluate the efficacy of the EuroSCORE II in anticipating the mortality in patients experiencing cardiac surgery.Subjects and methods: Cross-sectional observational study from a sample of 101 cardiac surgery patients was conducted to evaluate the outcomes (length of stay at ICU and hospital and mortality) of postoperative cardiac surgery in relation to EuroSCORE II at Punjab Institute of Cardiology Lahore from 22nd April, 2016 to 15th December, 2016.Results: Mean values of WBCs, serum creatinine and bilirubin total were significantly increased from preoperative to postoperative-I and a minor decrease on the postoperative II readings whereas mean values of hemoglobin and platelets constantly (p-value
Keywords: EuroSCORE II; Cardiac Surgery; Outcomes, Mortality; Risk.